Achieving synergy of mechanical isotropy and tensile properties by constructing equiaxed microstructure in as-printed Ti alloys. (May 2023) - Wang, S.X.; Li, S.F.; Gan, X.M.; Zheng, R.; Ye, D.; Misra, R.D.K.; Kondoh, K.; Yang, Y.F.
ABSTRACT: The grain refinement approach of generating constitutional supercooling by simultaneously introducing growth restricting solutes, Ni and B, is proposed to eliminate columnar prior-β grains and modify α-laths to equiaxed grains in as-printed Ti alloys. The aim is to achieve the synergy of reducing mechanical anisotropy and retaining good ductility at specified levels of strength. A new type of Ni-B-coated Ti powder was designed to confirm the hypothesis and accomplish the objective. Under the synergistic effect of Ni and B, columnar to equiaxed transition and ultrafine grain size of prior-β grains were achieved. This significantly restricted the growth of α-lath and enabled us to obtain equiaxed α-Ti microstructure. The fundamental outcome inspired us to develop a new Ti-Ni-B alloy with practically permissible mechanical anisotropy and excellent tensile properties. The optimized as-printed Ti-1.2Ni-0.06B alloy exhibited excellent comprehensive tensile properties with strength of 970 MPa and elongation of 10.7%. Graphical abstract: Image, graphical abstract